Simply small groups differentiating literacy learning in any setting - Diller, Debbie 1954- (Corwin literacy, 2022)
"Simply Small Groups will show the basics that teachers need to know in order to teach effectively in a small group setting, regardless of whether that is in a traditional classroom, in a virtual classroom, or a combination of the two. The focus here is on assessing students' assets and challenges, and understanding how to teach them in a small-group setting to help them progress as readers"--